The Integration of Maṣlaḥah into Islamic Economic Law through the policy of Halal and Tayyib Certification in Indonesia - Faridatun Nisa; Helmi Fitriansyah; Chaerul Saleh (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This article examines the integration of the concept of maṣlaḥah (public interest) within Islamic economic law through the implementation of halal and ṭayyib certification policies in Indonesia. The study aims to analyse the strategic role of these certifications in realising the values of maṣlaḥah and their implications for public welfare. Employing a qualitative approach through library research, this study draws upon scholarly literature, Islamic legal texts, national legislation, and relevant certification policies, particularly following the enactment of Law No. 33 of 2014 concerning Halal Product Assurance in Indonesia. The findings indicate that halal and ṭayyib certifications function not only as instruments of compliance with religious norms, but also as mechanisms for protecting consumer health, ensuring food safety, and promoting environmental sustainability—thus directly supporting the realisation of maṣlaḥah. The main contribution of this research lies in providing a conceptual framework that connects certification mechanisms with the normative principles of Islamic economic law, while offering a basis for strengthening public policy and regulatory systems in Indonesia towards a just, ethical, and sustainable economy grounded in Islamic values